2017
DOI: 10.1186/s12906-017-1913-y
|View full text |Cite
|
Sign up to set email alerts
|

Conessine as a novel inhibitor of multidrug efflux pump systems in Pseudomonas aeruginosa

Abstract: Background Holarrhena antidysenterica has been employed as an ethnobotanical plant for the treatment of dysentery, diarrhoea, fever, and bacterial infections. Biological activities of the principle compound, conessine including anti-diarrhoea and anti-plasmodial effects were documented. Our previous study reported potency of Holarrhena antidysenterica extract and conessine as resistance modifying agents against extensively drug-resistant Acinetobacter baumannii. This study aimed to investigate (i) whether cone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 24 publications
(31 reference statements)
0
42
0
1
Order By: Relevance
“…Many compounds extracted from the plant were introduced as EPI which inhibited bacterial pathogens. These compounds affected different efflux pumps including: MexAB-OprM in Pseudomonas aeruginosa; Nor A in Staphylococcus aureus, Bacillus cereus, Staphylococcus epidermidis, and Salmonella enteritidis; ND in Escherichia coli and Food-borne pathogens; and Msr A and Tet K in S. epidermidis [34][35][36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Many compounds extracted from the plant were introduced as EPI which inhibited bacterial pathogens. These compounds affected different efflux pumps including: MexAB-OprM in Pseudomonas aeruginosa; Nor A in Staphylococcus aureus, Bacillus cereus, Staphylococcus epidermidis, and Salmonella enteritidis; ND in Escherichia coli and Food-borne pathogens; and Msr A and Tet K in S. epidermidis [34][35][36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Conessine (HF1C) is a well-established constituent of H. floribunda [ 19 ]. Although the antibiofilm inhibitory property of H. floribunda and its constituents was not previously investigated, a recent study demonstrated the resistance-modifying ability of conessine through the inhibition of multidrug efflux pumps [ 35 38 ]. Another study has shown that compounds with efflux pump inhibition may also cause biofilm disruption [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence suggests that H. antidysenterica steroidal crude extract, and conessine may be acting as EPIs [ 19 , 20 ]. The steroidal extract and the alkaloid conessine have recently been reported to enhance antibiotic activity due to interference with the AdeIJK efflux pump in A. baumannii [ 19 ] which is functionally equivalent to the MexAB-OprM pump of P. aeruginosa [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The steroidal extract and the alkaloid conessine have recently been reported to enhance antibiotic activity due to interference with the AdeIJK efflux pump in A. baumannii [ 19 ] which is functionally equivalent to the MexAB-OprM pump of P. aeruginosa [ 30 ]. Furthermore, conessine restored antibiotic susceptibility to an otherwise resistant P. aeruginosa strain that overexpressed the MexAB-OprM efflux pump [ 20 ]. The data reported in the present study does not demonstrate that either the steroidal extracts or conessine are EPIs but is consistent with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation